Men and women who made America great - Basini, Eugene C. (River Forest, Ill. Laidlaw Brothers, 1975)
Biographical sketches of men and women instrumental in various aspects of American history from early exploration to music and dance.
Includes index.
Keywords: North America -- Biography -- Juvenile literature; United States -- Biography -- Juvenile literature; United States -- Biography